The Effect of Principal Leadership and Islamic Religion Teacher Performance on Student Learning Outcomes at SMP Negeri 2 Jogonalan - Rahmanto, Shodiq; Nashir, Muhammad Ja'far; Amin, Lailla Hidayatul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The purpose of this study is to describe the effect of the principal's leadership style on student learning outcomes at SMP Negeri 2 Jogonalan, to describe the effect of teacher performance on student learning outcomes at SMP Negeri 2 Jogonalan, to find out how much influence the principal's leadership and the performance of Islamic Religion teachers on student learning outcomes at SMP Negeri 2 Jogonalan. This research uses descriptive correlational research method with quantitative approach. In this study, there are independent variables (X), namely principal leadership or X1 and Islamic Religion teacher performance or X2 and the dependent variable (Y), namely student learning outcomes. The research was conducted at SMP Negeri 2 Jogonalan from August to October 2023. The population in this study were all students at SMP Negeri 2 Jogonalan. The sampling technique used in this study was random sampling technique because the research sample was randomly selected from the entire population, namely 50 samples. Data collection techniques using closed questionnaires and documentation. The results showed that the principal's leadership has a significant effect on student learning outcomes at SMP Negeri 2 Jogonalan, showing t count = 2.122, so the effect of X1 (Principal Leadership) on Student Learning Outcomes is significant. Islamic Religious Education Teacher Performance has a significant effect on student learning outcomes at SMP Negeri 2 Jogonalan, showing t count = 2.079, then the effect of X2 Teacher